Riba Usaha Koperasi: Studi Interdisipliner terhadap Legalitas Riba dalam Ulangan 23:20 dari Perspektif Preferential Option for the Poor - Ndruru, Terifosa (Faculty of Theology Duta Wacana Christian University, 2025)
AbstractFor a long time, the practice of charging interest on loans has been a means for capitalists to amass wealth, often at the expense of debtors who suffer economic injustice in an interest-driven economy. This is evident in the independent cooperative initiatives by some church members in Tangerang. Consequently, it is essential to examine the issue of interest from the viewpoints of economists, sociologists, and theologians. This research demonstrates that wholesale lending practices fail to enhance the economic conditions of low-income individuals. To address this, the study employs an interdisciplinary qualitative approach to explore the phenomenon as an economic, social, and theological issue. The goal of this research is to propose a solution for enhancing economic well-being without interest, drawing on Pedro Arrupe’s theory of preferential options for the poor. This theory stresses the importance of responsibility and solidarity with the impoverished by offering loans with low interest, as guided by Deuteronomy 23:20. AbstrakPinjaman uang dengan bunga telah lama digunakan sebagai alat untuk meningkatkan kekayaan pemilik modal, dan debitur telah menjadi korban ketidakadilan ekonomi atas sistem ekonomi riba karena keuntungan hanya di pihak kreditur, seperti yang dilakukan melalui usaha koperasi mandiri yang dilakukan oleh beberapa warga gereja di Tangerang. Itulah sebabnya persoalan riba perlu dikaji menurut pandangan para ekonom, sosiolog, dan teolog. Penelitian ini menegaskan bahwa praktik riba yang memberatkan tidak mampu membangun ekonomi orang miskin. Oleh karena itu, studi ini menggunakan metode kualitatif interdipliner yang menjelaskan fenomena riba sebagai masalah ekonomi, sosial, dan teologis. Penelitian ini bertujuan untuk memberikan solusi untuk meningkatkan kesejahteraan ekonomi tanpa riba yang memberatkan berdasarkan teori Pedro Arrupe tentang preferential option for the poor, yang menekankan tanggung jawab dan solidaritas kepada orang miskin melalui pemberian pinjaman tanpa riba atau dengan riba ringan berdasarkan Ulangan 23:20.